2011
DOI: 10.1152/ajprenal.00014.2011
|View full text |Cite
|
Sign up to set email alerts
|

A novel lipid natriuretic factor in the renal medulla: sphingosine-1-phosphate

Abstract: Zhu Q, Xia M, Wang Z, Li P, Li N. A novel lipid natriuretic factor in the renal medulla: sphingosine-1-phosphate. Am J Physiol Renal Physiol 301: F35-F41, 2011. First published April 6, 2011 doi:10.1152/ajprenal.00014.2011.-Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid metabolite formed by phosphorylation of sphingosine. S1P has been indicated to play a significant role in the cardiovascular system. It has been shown that the enzymes for S1P metabolism are expressed in the kidneys. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 38 publications
6
41
0
Order By: Relevance
“…detected in whole kidney tissue, renal medulla, and glomeruli 11,12 ; however, the distribution of S1P receptor expression in the renal microvasculature has not been studied. We demonstrate here that both S1P1 and S1P2 proteins are abundantly present in isolated preglomerular microvessels, whereas S1P3, S1P4, and S1P5 receptor protein expression was not detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…detected in whole kidney tissue, renal medulla, and glomeruli 11,12 ; however, the distribution of S1P receptor expression in the renal microvasculature has not been studied. We demonstrate here that both S1P1 and S1P2 proteins are abundantly present in isolated preglomerular microvessels, whereas S1P3, S1P4, and S1P5 receptor protein expression was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of detection of S1P4 receptors in renal microvessels agrees with the findings of Ota et al, who reported positive staining for S1P4 receptor protein in pulmonary arteries but not intrarenal arteries. 39 Furthermore, to distinguish between endothelial or tubular cell expression, 11,12 we isolated MVSMCs from preglomerular microvessels. Consistent with Western blot data, S1P1 and S1P2, but not S1P3, receptors were strongly detected in isolated MVSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the expression of SphK1 as well as S1PRs was demonstrated in whole kidney and in isolated renal cells. In the rat, S1P1-3 are more abundant in the medullary than in the cortical CD [189] . The cellular localization (i.e., apical or basolateral) remains uncertain to date.…”
Section: "Novel" Gpcr That Inhibit Sodium Absorption In the Distal Nementioning
confidence: 91%
“…This suggests that thenatriuretic and diuretic effects of S1P1 stem from PC. Finally it can also be noted that a S1P1 antagonist has anti-natriuretic properties [189] . The main characteristics of glomerulonephritis (proliferation of mesangial cells, stimulation of matrix production and inflammation) may involved the SphK1/ S1P signaling system.…”
Section: "Novel" Gpcr That Inhibit Sodium Absorption In the Distal Nementioning
confidence: 99%